Implikasi dasar liberalisasi perkhidmatan kewangan terhadap perbankan Islam di Malaysia / Noor Aznaim Abd Latib - Noor Aznaim, Abd Latib (2017)
Malaysian government has implemented financial liberalization policy since 30 years ago. This financial liberalization policy has been implemented in stages since 1970, and the latest was on 27th of April 2009. Liberalization policy in year 2009 is more focused on the Islamic finance sector. Based on the above discussion, several issues have been raised related to the effectiveness of implementing financial policy, even though it is a good policy that lunges positive injection for Islamic banking. Based on the above problems, the main objective of this study is to analyse the effectiveness of the financial liberalization policy towards Islamic banking in Malaysia with reference to the aspects of capital, liquidity and asset quality as a stability measured in the banking system. To achieve the above objectives, this study uses the estimation method of panel data set (combination of time series data and cross section) that combines 11 full fledge Islamic banks in Malaysia between the year 2000 until 2013. This study found that financial liberalization will facilitate the entry and exit of foreign investors while stimulating the formation of capital in the banking system. Secondly, there will be an increase in liquidity thus encouraging people to deposit their money. This will also make it easier for the people to manage their business due to impact on service quality and diversity of products offered by banks, as a result of competition between banks. Finally, liberalization will also lead to a better efficiency of risk management thus indirectly reducing the losses incurred by banks and increase the profit.